2004
DOI: 10.1002/ajh.20183
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and liver tumors: Fanconi's anemia and non‐Fanconi's conditions

Abstract: The association between anabolic androgenic steroids and liver tumors was first noted in patients with Fanconi's anemia (FA). The hypotheses which led to this review were as follows: (1) androgen-treated individuals who do not have FA are also at risk of liver tumors; (2) parenteral as well as oral androgens may be responsible for liver tumors; (3) FA patients develop liver tumors after smaller and briefer androgen exposure than non-FA individuals; (4) the risk of hepatic neoplasms may depend on the specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(141 citation statements)
references
References 60 publications
4
137
0
Order By: Relevance
“…33 Hematopoietic growth factors may be useful in BMF. However, splenic peliosis and splenic rupture have been reported in two individuals with DKC, receiving androgens and G-CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Hematopoietic growth factors may be useful in BMF. However, splenic peliosis and splenic rupture have been reported in two individuals with DKC, receiving androgens and G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,32 Although a trial of androgen therapy (for example, oxymetholone) may be considered first, while the preparation for allografting is underway. 33,34 The Working Party Severe Aplastic Anemia of the European Blood and Marrow Transplantation is conducting an extensive database and literature review of transplants performed worldwide in DKC. (E. Korthof, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Although they can be used therapeutically at low doses to treat aplastic anemia (Velazquez et al, 2004), osteoporosis (Berning et al, 2001;Kilbourne et al, 2007), and as antitumor agents in breast cancer (von Bueren et al, 2007) in women, the beneficial health effects of such doses contrast with the risks associated with excessive self-administered doses by women athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with no available donor, androgen treatment may improve blood cell counts [8]. It is now well-established that androgen treatment is a risk factor for liver abnormalities in both FA and non-FA patients [9][10][11][12][13][14]. Some studies have previously reported hepatic tumors in patients with FA [9,15,16], but little is known concerning other abnormalities of the livers of these patients.…”
mentioning
confidence: 99%
“…Androgen treatment is a well-known risk factor for liver tumors [11] and the three patients with liver tumors described here received androgen treatment for 4, 6, and 30 years, respectively.…”
mentioning
confidence: 99%